Impact of Biodiesel Demand on the Malaysian Palm Oil Market - Applanaidu, Shri Dewi (2010)

(untitled)
One of the new elements in the palm oil market is the growing demand for this commodity as a feedstock to biodiesel production. This new development is affecting the dynamics of the market, in particular, the supply and demand sectors of this commodity. The general objective of the study is to investigate the impact of biodiesel demand on the Malaysian palm oil market. The specific objectives are: (i) to develop an econometric model of the Malaysian palm oil market,(ii) to examine the relationship between crude oil and palm oil and eventually to examine the impact of world crude oil prices on Malaysian palm oil market, (iii) to examine the impact of biodiesel demand on Malaysian palm oil market (supply, demand and price) and (iv) to recommend some policy options to ensure the competitiveness of Malaysian biodiesel industry. The study uses econometric modelling involving simultaneous system of nine structural equations and four identities. The estimators of the structural parameters were derived with the two stage least squares (2SLS) method using annual data for the period 1976-2009. The structural relationships were validated with Theil’s inequality coefficients (U-Theil), the root mean squares percentage errors (RMSPE) and turning points. The 2SLS model was used for simulation of counterfactual and scenario analysis. The econometric simulation consists of two parts. The first part consists of counterfactual analysis. A ‘shock’ was injected into the system by indicating two levels of crude oil prices (i.e., 20 percent increase and decrease in crude oil prices; 30 and 60 percent increase in biodiesel demand). The impact of these change on endogenous variables were then estimated. The second part was the ex-ante simulation scenario analysis. The forecast was carried out for the years 2010 to 2015 before the ex-ante simulation exercise. The results of the regression analyses show that relative price between palm oil and natural rubber, interest rate, government development expenditure on agriculture and time trend are important factors affecting palm oil production. The domestic consumption is significantly affected by palm oil price, income, price of soybean oil and lagged domestic consumption. All the variables in the export demand of palm oil for biodiesel equation including palm oil world price, exchange rate, rapeseed oil price, biodiesel importing countries GDP and price of crude oil are statistically significant. Meanwhile, the export of palm oil for non-biodiesel purpose is significantly affected by palm oil world price, exchange rate, soybean oil price, world income and presence of a lagged dependent variable. The palm oil stock, palm oil world price, biodiesel demand and lagged domestic price are the main important variables influencing the domestic price of palm oil. Meanwhile, the world price is affected by soybean price, world income and lagged world price. The coefficient of the world stock variable is negative and it follows the expected sign. This oefficient, however, is not statistically significant. A counterfactual analysis of a sustained 20 percent increase in crude oil prices predicts a direct effect of a 22.94 percent increase in export of palm oil for biodiesel. The indirect effects through the export of palm oil for biodiesel transmission channels are: 11.43 percent decrease in stock, 25.03 percent increase in Malaysian domestic palm oil price, 0.18 percent increase in crude palm oil production, 0.72 percent decrease in domestic consumption and there is also 26.33 percent increase in world price. Meanwhile an ex-ante simulation suggests that the directions are consistent with the theory and counterfactual analysis but the magnitude of changes are smaller. A sustained 30 percent increase in biodiesel demand of counterfactual analysis predicted a direct effect of a 27.94 percent increase in Malaysian domestic palm oil price. The domestic price acted as a transmission channel which results in a 1.18 percent increase in crude palm oil production,0.45 percent decrease in domestic consumption, 0.43 percent increase in stock, 20.77 percent decrease in world price, 2.52 percent increase in export of palm oil for biodiesel and a 12.95 percent increase in imports. An ex-ante simulation suggests that the directions are consistent with the theory and counterfactual analysis but the magnitude of changes are smaller. The econometric simulations suggest that the biodiesel demand does bring positive economic impact on selected sub-sectors of the palm oil industry such as it encourages export, increase domestic price and hence to some extent production. Since the study suggest that production of palm oil as a feedstock to biodiesel in Malaysia increase in response to the biodiesel demand future expansion may be hindered because of land constraint. As an option, Malaysia can invest offshores such as in Indonesia, Papua New Guniea and selected African countries.